EP01 Audit of the monitoring and documentation of DAS28 score in patients prescribed high cost DMARDs for rheumatoid arthritis every 6 months according to British Society for Rheumatology guidelines. (20th April 2020) - Tsoi, Kevin F. W; Sahni, Amit; Selvanayagam, Bianka; Memon, Muhammad
Abstract: Background: DAS28 is a measure of disease activity in rheumatoid arthritis (RA) which is comprised of the number of tender and swollen joints, inflammatory markers and visual analogue score. Both NICE and British Society of Rheumatology recommend DAS28 is recorded at least every 6 months in patients with RA, to monitor disease activity and ensure adequate response to treatment. CCG mandate 6 monthly DAS28 scores for patients on high cost DMARDs in order to secure funding. Absence of DAS28 scores results in CCGs refusing to fund treatment at the expense of the Trust. Methods: Our aim was to review whether a DAS28 was documented in every consultation and if it meets the audit standard of a review every 6 months. If the 6 month target is not met, to understand the reason for this and to suggest ways to meet the standard. Blueteq is the software used to identify all patients with a diagnosis of RA between January 2014 and January 2019 at Royal Surrey County Hospital (RSCH). Clinic letters were reviewed to identify whether a DAS28 score was recorded, the date it was recorded and whether this was done within 6 months. Results: In total, 207 patients are prescribed high cost DMARDs for RA at RSCH. 166 (80%) patients have a documented DAS28, but 41 (20%) patients did not have a documented DAS28. 14 (7%) patients have a documented DAS28 at least 6 monthly. 152 (73%) patients did not meet the audit standard. Conclusion: Documentation of DAS28 in clinic letters at RSCH does not meet the audit standard. However, these scores have been recorded on Blueteq in order to satisfy CCG requirements. There needs to be consistency in where DAS28 is recorded. Factors contributing to an absence of a documented DAS28 in clinic letters include: no recent inflammatory markers, patients not receiving clinic appointments scheduled at the correct interval, patients not attending clinic, limited follow-up clinic capacity. DAS28 documentation can be improved by incorporating a table into each rheumatology clinic letter template. On initiation of a high cost therapy, the importance of regular blood monitoring and clinic attendance should be reiterated to patients as well as to the appointments booking team. An early arthritis pathway already exists, which can be extended to incorporate a high cost DMARD pathway detailing how to achieve target documentation. Disclosures: K.F.W. Tsoi: None. A. Sahni: None. B. Selvanayagam: None. M. Memon: None.